Response of Growth and Yield of Pakcoy Mustard Plants (Brassica rapa L.) to the Application of Growth Regulatory Substances - Manu, Charisal Matsen; Bunyani, Nur Aini; Tay, Ratnasari Renggi; Kerihi, Eka Citra Gayatri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Vegetables are a broad category of plant foods that typically have a high water content and can be eaten fresh or cooked or prepared in specific ways. The purpose of this study is to determine the effects of growth regulators on Pak Choy mustard plants as well as the plants' responses to them. Three iterations of the RAL research methodology were conducted. Using a dosage of 200 milliliters of coconut water, 400 milliliters, and 600 milliliters. through the combination of four therapies. The results of the research show that the administration of growth regulators can have a good influence on plant height, number of leaves, leaf area and fresh weight of roots per sample. Suggestion: This research is expected to contribute to a sustainable agricultural system by maximizing the use of environmentally friendly natural growth regulators.